Seasonal Variations in the Small Phytoplankton Contribution to the Total Primary Production in the Amundsen Sea, Antarctica. Issue 11 (30th November 2019) - Lim, Yu Jeong; Kim, Tae‐Wan; Lee, SangHoon; Lee, Dabin; Park, Jisoo; Kim, Bo Kyung; Kim, Kwanwoo; Jang, Hyo Keun; Bhavya, P.S.; Lee, Sang H.
Abstract: The importance of small phytoplankton in warming and stratified water conditions has been emphasized, but little information on the small phytoplankton contribution is currently available in the Southern Ocean. In this study, we analyzed temporal variations in the carbon uptake rates of large and small phytoplankton and the small phytoplankton contributions to the total primary production. The data were collected in the Amundsen Sea polynya region using three different field observations (early January, January–February, and February–March) from 2012 to 2016. The total primary production in the polynya region decreased from 0.84 ± 0.18 g C·m −2 ·day −1 in early January to 0.19 ± 0.04 g C·m −2 ·day −1 in February–March, which is typical of the seasonal variation in the primary production of phytoplankton in the Amundsen Sea. In contrast, the small phytoplankton contributions to the total carbon uptake rates increased considerably from early January (14.9 ± 8.4%) to February–March (50.8 ± 18.4%) in the polynya region. This substantial increase of small phytoplankton contribution was not caused by increasing biomass and the specific uptake rates of small phytoplankton, but rather by seasonally declining biomass and the specific uptake rates of large phytoplankton during the study period. The overall contribution (25.5 ± 15.7%) of small phytoplankton to the primary production in the polynya region based on the three different time observations is significantly higher than the previous result (14.9 ± 8.4%) based on one time observation. Therefore, a seasonal variation in the small phytoplankton contribution in the Amundsen Sea should be considered in further studies. Key Points: Small phytoplankton contributions to the total carbon uptake rates increased considerably in late austral summer season Seasonally increasing small phytoplankton contribution was by declining biomass and specific uptake rate of large phytoplankton Small phytoplankton contribution to the primary production in this study is significantly higher than the previous result